2005
DOI: 10.1158/0008-5472.can-04-1975
|View full text |Cite
|
Sign up to set email alerts
|

Administration of IFN-α Enhances the Efficacy of a Granulocyte Macrophage Colony Stimulating Factor–Secreting Tumor Cell Vaccine

Abstract: IFN-A is approved for the treatment of multiple cancers. Its pleiotropic properties include inhibition of proliferation and angiogenesis and induction of apoptosis. Type I IFNs also exert immunomodulatory effects, which make it an appropriate candidate to combine with cancer vaccines. The studies reported herein show that 50% of mice reject established B16 tumors following treatment with the combination of a granulocyte macrophage colony-stimulating factor-secreting tumor cell vaccine (B16.GM) and subclinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 52 publications
(60 reference statements)
0
16
0
Order By: Relevance
“…36 Also a combination of IFN-a and GM-CSF secreting tumor vaccine was shown to significantly enhance the potency of the immunotherapeutic effect. 37 The expression of the HN protein of NDV at the cell surface of the ATV-NDV tumor vaccine 5 as well as the replication of NDV within these cells may be of central importance for the induction of IFN-a at the vaccination site and consequently for the observed antitumor response in clinical studies based on NDV tumor vaccine. 16 Here, we show that a tumor vaccine obtained by irradiation and infection with rec(GM-CSF) induces a stronger IFN-a response in human monocytes and PDCs than a vaccine infected with the virus without incorporated foreign gene.…”
Section: Ndv As Vector For Therapeutic Genes In Tumor Therapymentioning
confidence: 99%
“…36 Also a combination of IFN-a and GM-CSF secreting tumor vaccine was shown to significantly enhance the potency of the immunotherapeutic effect. 37 The expression of the HN protein of NDV at the cell surface of the ATV-NDV tumor vaccine 5 as well as the replication of NDV within these cells may be of central importance for the induction of IFN-a at the vaccination site and consequently for the observed antitumor response in clinical studies based on NDV tumor vaccine. 16 Here, we show that a tumor vaccine obtained by irradiation and infection with rec(GM-CSF) induces a stronger IFN-a response in human monocytes and PDCs than a vaccine infected with the virus without incorporated foreign gene.…”
Section: Ndv As Vector For Therapeutic Genes In Tumor Therapymentioning
confidence: 99%
“…10 GM-CSF-based immunotherapy has been shown to increase the survival in several experimental rat and mouse glioma models. 3,4,11,12 Peripheral vaccination with GM-CSF is evaluated in several clinical trials for various types of cancer, [13][14][15] and so far preliminary results have shown low toxicity and activation of an immune response. IFNg is a multifunctional cytokine that recently has been linked to immune surveillance of developing tumors.…”
mentioning
confidence: 99%
“…We propose that the efficiency of this treatment modality arises from the synergy between GM-CSF production and IFN-a/b induction for induction of anti-cancer CD8 T cells. 24,36,37 As with most intra-tumoral gene delivery systems, the level of transfection in vivo is likely to be an important factor. 4 We have tested the transfection efficiency of a number of tumour cell lines in vitro and found that at MOI ¼ 10, 1-5% of CT26 cells and 10-20% of B16-OVA cells are transfected, with Vero and BHK cell transfection usually reaching 50-90% (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…2 Dendritic cell attraction and maturation appear to be the critical components of GM-CSF's mechanism of action, 21,22 with tumour destruction largely dependent on anti-cancer CD8 T cells. 20,[23][24][25] IFN-a/b is approved for the treatment of several cancers and mediates a range of direct activities against cancers, the best known of which are slowing of the cell cycle, promotion of differentiation, anti-angiogenesis and promotion of apoptosis. 26 IFN-a/b is also an important link between the innate and adaptive immune systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation